Maternal Stress and Problem‐Solving Skills in a Sample of Children with Nonorganic Feeding Disorders. Issue 3 (18th January 2013) - Martin, Clarissa I.; Dovey, Terence M.; Coulthard, Helen; Southall, Angela M.
ABSTRACT This study compared the problem‐solving strategies among 20 mothers whose infants were diagnosed with a feeding disorder against 20 matched controls. The mothers from the two groups were matched for age and level of education. All mothers completed two questionnaires: the Behavioral Pediatric Feeding Assessment Scale and the Parenting Stress Index (R.R. Abidin, 1990). To measure maternal problem‐solving skill, the Parent Means‐End Problem‐Solving Instrument (D.M. Bryant & B.H. Wasik, 1994) was administered. As expected, statistically significant differences were related to the number and frequency of feeding problems reported and difficulties with mealtime management. Furthermore, mothers of children with a diagnosed feeding disorder demonstrated fewer problem‐solving skills and made use of more "high‐control solutions" (e.g., forcing the child to comply or punishing the child). In contrast, parents of children without feeding disorders preferred to implement more indirect problem‐solving strategies (e.g., planning to remove the child from the situation). Mounting evidence has suggested that difficulties in parenting a child with a diagnosed nonorganic feeding disorder stem from both child‐ and parent‐related factors. The current study provides tentative early evidence for the role of maternal high‐controlling problem‐solving strategies in a small sample of children diagnosed with this disorder.